Will Tirzepatide become a game-changer in the pharmacological treatment of obesity? - literature review - Aleksandra Doryń; Kinga Woźniak; Magdalena Jung; Maximilian Jung; Patryk Hedesz; Klaudia Warzycka; Monika Gardian-Baj; Alicja Szczerbiak; Wiktoria Ulicka; Katarzyna Kuśmierczyk; Karolina Maliszewska (Journal of Education, Health and Sport, 2024)
Introduction and objective: Obesity has become an important public health issue in Poland. Furthermore, it is one of the most common preventable causes of diseases and mortality. Pharmacological methods of treating obesity have been developing significantly in recent years.Tirzepatide is a new dual incretin receptor agonist that activates both GIP (glucose-dependent insulinotropic polypeptide) and GLP-1 (glucagon-like peptide-1) receptors. The aim of this review is to assess the effectiveness of this medication in reducing body weight.